TANGGUNG JAWAB PEMULIHAN HUTAN MANGROVE YANG DIRUSAK: TINJAUAN STRICT LIABILITY PASAL 88 UNDANG-UNDANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - I Komang Sumika Adinata; Komang Febrianayanti Dantes; I Gusti Ayu Apsari Hadi (Jurnal Ilmu Hukum Sui Generis, 2026)
Mangrove forests in Indonesia's coastal areas are shrinking due to conversion into business areas such as lodging, fish ponds, and residential areas. Mangrove destruction triggers coastal abrasion, a decline in marine biota populations, and weakens the livelihoods of coastal communities. To mitigate this damage, Law Number 32 of 2009 stipulates the principle of absolute liability in Article 88, which requires business actors to bear all consequences of environmental damage without needing to prove intent or negligence. However, following amendments through Law Number 6 of 2023, the wording of Article 88 has changed, raising questions about the validity of this norm in practice. This study uses a normative legal approach by examining environmental legal regulations and concepts. Data were obtained from library materials in the form of laws, court decisions, and literature, and then analyzed qualitatively. The results of the study show that Article 88 still imposes full responsibility on business entities that damage mangroves, including the obligation to restore the environment. However, in judicial practice, the implementation of this principle has not been optimal. The new formulation of Article 88 has led to differing interpretations among judges regarding the criteria for a serious threat and the link between business activities and damage. The resulting decisions still tend to involve monetary payments, while orders to replant and monitor mangroves for a specified period are still rarely issued. Therefore, it can be concluded that the principle of strict liability in Article 88 has not been able to significantly encourage mangrove restoration after damage by commercial activities. Clear guidance for judges, detailed indicators of mangrove damage in subsequent regulations, and awareness among business actors are needed to incorporate strict liability into their calculations from the outset of project planning.